Analysis of the complete organellar genomes of Palmaria decipiens (Palmariaceae, Rhodophyta) from Antarctica confirms its taxonomic placement in the genus Palmaria - Danilo E. Bustamante; Jeffery R. Hughey; Martha S. Calderon; Andres Mansilla; Juan P. Rodriguez; Fabio Mendez (Mitochondrial DNA. Part B. Resources, 2020)
Palmaria decipiens (Reinsch) R.W.Ricker is a ecologically important red seaweed restricted to high latitudes of the southern hemisphere. Here, we contribute to the bioinformatics and evolutionary systematics of the Palmariales by performing high throughput sequencing analysis on a specimen of P. decipiens from the western Antarctic Peninsula. The P. decipiens mitogenome is 26,645 base pairs (bp) in length and contains 49 genes (GenBank accession MN967053) and the plastid genome is 193,007 bp and contains 245 genes (GenBank accession MN967052). The mitogenome and plastid genome of P. decipiens are similar to P. palmata from Japan in pairwise genetic distances (93.71% and 98.14%, respectively), and P. palmata from the Maine, USA (87.45% and 94.57%, respectively). The genomes of P. decipiens showed high gene synteny with P. palmata, however several tRNA differences are documented. Organellar genome content and phylogenetic analyses of P. decipiens supports its placement in the genus Palmaria.